Isokinetic performance of ankle evertor and invertor muscles in adolescent female volleyball athletes - Leandro Viçosa Bonetti; Nicole Coulon Grisa; Juliete Palandi; André Luis Temp Finger; Thiago De Marchi; Gerson Saciloto Tadiello (Motriz: Revista de Educacao Fisica, 2018)
Abstract Aims: This study aimed to analyze the muscular performance of evertor and invertor ankle muscles of adolescent volleyball athletes. Methods: The information provided by database concerning the isokinetic evaluation of ankle muscles from 20 female volleyball players between the ages of 14-17 years old were analyzed. The isokinetic dynamometer was used in a concentric-concentric mode for the ankle evertor and invertor muscles at angular velocities of 60°/s, and 180°/s. Results: Seven athletes had suffered ankle sprains (6 affected the non-dominant limb and all were lateral ankle sprain) in the one year prior to the isokinetic evaluation. The isokinetic results demonstrated that the mean peak torque values for eversion of the non-dominant limb were significantly lower in comparison to the dominant limb at 60°/s. Moreover, although no difference was observed in the average values of the evertor/invertor ratio between the limbs, the ratios were below the values suggested by the literature. Conclusion: We believe that although the athletes reported no ankle injury and no pain in the previous assessment month, the isokinetic results of the non-dominant limb seemed to be directly related to previous ankle sprains injuries in inversion of this limb. The athletes had similar results to those of subjects clinically diagnosed with ankle joint instabilities despite their being active in sports at the moment of the assessment.